Identifying tests related to breast cancer care in claims data. Issue 6 (18th November 2019) - Franc, Benjamin L.; Thombley, Robert; Luo, Yanting; Boscardin, W. John; Rugo, Hope S.; Seidenwurm, David; Dudley, R. Adams
Abstract: To develop a method for calculating rates of testing for breast cancer recurrence in patients who have already undergone initial treatment for breast cancer, we calculated rates in a cohort of Medicare breast cancer patients and an age‐matched noncancer cohort. We first used only tests with claims including diagnosis codes indicating invasive breast cancer and then used all tests regardless of diagnosis code. For each method, we calculated testing rates in the breast cancer cohort above the background rate in the noncancer population. The two methods provided similar estimates of testing prevalence and frequency, with exception of prevalence of CT.